Inclusive Learning at ABA Bebekan Kindergarten: Curriculum and Environment Adaptation: Pembelajaran Inklusif di TK ABA Bebekan: Adaptasi Kurikulum dan Lingkungan - Larasati , Laila Rohma; Rocmah, Luluk Iffatur (Indonesian Journal of Education Methods Development, 2025)
General Background : The implementation of inclusive education is a crucial issue in modern education to ensure all children's right to learn is fulfilled. Specific Background : This study specifically describes the implementation of inclusive learning at TK ABA Bebekan, focusing on curriculum adjustments, the use of inclusive learning technology, and the creation of an inclusive learning environment. Knowledge Gap : While the concept of inclusive education is well-known, there is a lack of detailed descriptive case studies that can serve as a practical guide for other institutions. Aims : The purpose of this research is to provide a comprehensive analysis of how TK ABA Bebekan implements inclusive learning. Results : The findings indicate that the implementation follows a systematic process, including child identification, assessment, and curriculum adjustment. This process also incorporates inclusive learning technology and a supportive environment. The study found no differences in implementation except for learning outcomes. Novelty : The research's novelty lies in its detailed and practical description, which can serve as a model for other educational institutions. Implications : The findings are expected to serve as a valuable reference for schools beginning to apply inclusive learning programs, emphasizing that inclusive practices can be implemented effectively without differentiation, except for adjusted learning outcomes. Highlights : This research describes the implementation of inclusive education at TK ABA Bebekan. The implementation process involves child identification, assessment, and curriculum adjustments. The study provides a practical reference for other educational institutions looking to adopt inclusive learning programs. Keywords : Inclusive Education, Curriculum Adjustment, Inclusive Environment, Educational Technology, Early Childhood